Role of tumor necrosis factor-α in coronavirus disease 2019-associated kidney injury - PANDIT Roshan; LU Junyao; HE Liheng; BAO Yujie; JI Ping; CHEN Yingying; XU Jie; WANG Ying (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To identify relevant biomarkers for patients with coronavirus disease 2019-associated kidney injury (COVID-19-associated KI) and explore the mechanisms underlying the involvement of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) proteins in infection-related KI by affecting the interactions between renal cells and macrophages.Methods·A retrospective analysis was conducted on the clinical characteristics of COVID-19 patients with KI treated in Shanghai Ninth, People′s, hospital from December 2022 to February 2023. Serum levels of inflammatory factors and chemokines were measured by using enzyme- linked immunosorbent assay (ELISA). In vitro, human macrophage cell line THP-1 cells were stimulated with recombinant S1 subunit protein derived from SARS-CoV-2 spike protein. The cells and culture supernatants were collected to detect the levels of inflammatory factors and chemokines by using quantitative real-time PCR (qRT-PCR) and ELISA. Conditioned medium was prepared from the cell culture supernatants of S1-stimulated THP-1 cells and used to stimulate human renal epithelial cells (HK-2) in vitro to assess cytokine secretion. Antibody blocking experiments were performed to analyze the effects of the conditioned medium on the production of cytokines in HK-2 cells.Results·Among 39 patients with COVID-19, 8 (20.50%) had creatinine levels above the reference interval, which indicated the occurrence of KI. The levels of peripheral tumor necrosis factor-α (TNF-α) in the COVID-19 patient with KI group [(18.33±8.20) pg/mL] were significantly higher than those in the non-KI group [(11.88±6.50) pg/mL] (P=0.015). In vitro assay has shown that S1-spike protein stimulation promoted the level of gene transcription and production of TNF-α, interleukin-1β (IL-1β) and chemokine C-X-C motif ligand 10 (CXCL10) in THP-1 macrophage cells (P<0.001). Furthermore, the conditioned medium from S1-stimulated THP-1 cells promoted the secretion of TNF-α, IL-1β and CXCL10 by HK-2 cells (P=0.005). When anti-TNF-α antibody (Infliximab) was used to block TNF-α in the culture supernatants from S1-stimulated THP-1 cells, the secretion level of TNF-α by HK-2 cells decreased dramatically (P<0.001).Conclusion·TNF-α levels increase significantly in COVID-19 patients with KI, implying the significance of TNF-α in the occurrence of COVID-19-associated KI. In vitro experiments confirm that the S1 protein induces TNF-α secretion from THP-1 cells, leading to increased inflammatory responses in renal cells, which may contribute to the development of COVID-19-associated KI. Therefore, targeting TNF-α may become an alternative strategy to reduce the occurrence of COVID-19-associated KI.